2019
DOI: 10.3390/cells8060588
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin Exerts Anti-Proliferative Effects through Down-Regulating TIRAP/NF-κB Activity in Human Non-Small Cell Lung Cancer Cells

Abstract: Phycocyanin is a type of marine functional food additive, exerting a health care efficacy with no side effects. It has been shown that phycocyanin possesses anticancer function in non-small cell lung cancer (NSCLC) cells, but the underlying regulatory mechanism still remains unclear. Further investigation on the antineoplastic mechanism of phycocyanin would provide useful information on NSCLC treatment. In this study, we explored the in vitro function and mechanism of phycocyanin in three typical NSCLC cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…In the emerging field of host-directed therapies to intracellular pathogens, TLRs and their adaptor proteins were proposed as putative targets for the treatment of inflammatory disorders and to overcome microbial resistance ( 76 ). For example, Gefitinib, Phycocianin and other peptides were recently studied for their inhibiting effect on MAL in the context of endotoxic injury, lung cancers and autoimmune diseases, respectively, showing promising results ( 77 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the emerging field of host-directed therapies to intracellular pathogens, TLRs and their adaptor proteins were proposed as putative targets for the treatment of inflammatory disorders and to overcome microbial resistance ( 76 ). For example, Gefitinib, Phycocianin and other peptides were recently studied for their inhibiting effect on MAL in the context of endotoxic injury, lung cancers and autoimmune diseases, respectively, showing promising results ( 77 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…has also been reported ( Table 1 ) [ 38 , 40 ]. C-phycocyanin showed inhibitory activity in liver cancer cell lines (HepG2) [ 34 ], human leukemia cells (K562) [ 35 ] and against lung cancer cell lines (A549 and NSCLC) [ 36 , 37 , 38 ]. In another study, the phycocyanin from Limnothrix sp.…”
Section: Microalgae In Pharmaceuticalsmentioning
confidence: 99%
“…30,31 In NSCLC cells, knockdown of TIRAP expression by siRNA suppressed proliferation. 32 Cortactin (CTTN) has been identified as a biomarker of cancer metastasis due to its overexpression in various cancers, such as colorectal cancer, head and neck squamous cell carcinoma, among others. Results have suggested that CTTN inhibits the degradation of EGF and promotes the proliferation of CRC cells.…”
Section: Dovepressmentioning
confidence: 99%